2013
DOI: 10.1039/c2cp42750h
|View full text |Cite
|
Sign up to set email alerts
|

First-principles simulation of the absorption bands of fluorenone in zeolite L

Abstract: The absorption spectrum of fluorenone in zeolite L is calculated from first-principles simulations. The broadening of each band is obtained from the explicit treatment of the interactions between the chromophore and its environment in the statistical ensemble. The comparison between the simulated and measured spectra reveals the main factors affecting the spectrum of the chromophore in hydrated zeolite L. Whereas each distinguishable band is found to originate from a single electronic transition, the bandwidth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 74 publications
(134 reference statements)
5
63
0
Order By: Relevance
“…34). 218 The Frozen-Density Embedding Theory (FDET) was applied to examine both the induced shifts and shape broadening due to the dye-zeolite interactions. Most often, the zeolite environment is taken into account either via small clusters or via an embedding procedure.…”
Section: Optical Spectroscopymentioning
confidence: 99%
“…34). 218 The Frozen-Density Embedding Theory (FDET) was applied to examine both the induced shifts and shape broadening due to the dye-zeolite interactions. Most often, the zeolite environment is taken into account either via small clusters or via an embedding procedure.…”
Section: Optical Spectroscopymentioning
confidence: 99%
“…36,37 Also, configurations with the FL long axis perpendicular to the channel axis, where the FL carbonyl oxygen is far from the extraframework potassium cations, are much higher in energy than those aligned with the channel axis and become unstable at room temperature conditions, as evidenced by first-principles molecular dynamics. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 19 less than 4 kJ mol -1 (see Figure 8).…”
Section: Modeling Of Dry Zl/fl Adductsmentioning
confidence: 99%
“…Such an interaction was responsible of the stability of the fluorenone-ZL composite as well as of its substantial anisotropy, independently of the water content inside the channels. 36,37 All of these studies were performed by modeling a low dye loading in order to mimic the dye concentrations generally adopted in actual dye-ZL composites, which are normally below 0.5 molecules per unit cell. 23 The structure, properties and behavior of highly packed dye-ZL materials, 4 i.e., characterized by a high degree of dye loading, have never been explored to date, neither by experiment, nor by modeling.…”
Section: Introductionmentioning
confidence: 99%
“…The nanometric-scale geometry of zeolite pore systems allows the intensive use of zeolites in several fields such as in molecular separation processes and in heterogeneous catalysis [3,4]. Such ongoing progress in applications has been accompanied, in the latest years, by a deeper molecular-level understanding of the confined photoactive assemblies, which has been achieved through computational modelling [44][45][46][47][48][49][50], often combined with multi-technique experimental analyses [45,[50][51][52][53][54][55][56][57]. The key role of water in tuning the organization of the confined chromophores has been revealed [45,46,58], as well as the stabilizing effect of potassium cations in composites with carbonyl dyes [44,57,59].…”
Section: Introductionmentioning
confidence: 99%
“…We are interested in exploring whether the compression could favour a more ordered distribution of the dye molecules in the zeolite L channels and if this process leads to an improvement of the optical properties of the hybrid material. In fact, it has been shown that the properties of dye-zeolite systems depend on the molecular orientation, arrangement and packing inside the channel [14,15,20,[44][45][46]56,58], which control the guest-guest and host-guest interactions. To unravel and understand at molecular level the compression behaviour of the inclusion composites we adopted an integrated experimental-theoretical approach, based on the use of high pressure (HP) in situ synchrotron X-ray powder diffraction (XRPD) and ab initio molecular dynamics [98] simulations, which already captured a nice example of pressure-induced supramolecular organization in zeolites [97].…”
Section: Introductionmentioning
confidence: 99%